The Relationship Between Learning Motivation and Student Performance in Indonesian Language Subjects Among Fifth Grade Students of Public Elementary Schools in Gowa Re-gency (International Journal of Education and Literature, 2025)
The Correlation Between Learning Motivation and Academic Achievement in Indonesian Language of Fifth-Grade Students at SDN Samata, Gowa Regency. Undergraduate Thesis. Elementary School Teacher Education, Faculty of Teacher Training and Education, Muhammadiyah University of Makassar. This study employed a quantitative approach with an ex-post facto research design and a correlational test to investigate the relationship between learning motivation and Indonesian language achievement of fifth-grade students at SDN Samata, Gowa Regency. The population of this study consisted of 28 students of SDN Samata, Gowa Regency. Data was collected through questionnaires and documentation. Data analysis techniques used were descriptive statistics, normality test, and product moment correlation. The results showed that the learning motivation of fifth-grade students at SDN Samata, Gowa Regency was very strong, and their Indonesian language achievement was excellent. It can be concluded that there is a significant correlation between learning motivation and Indonesian language achievement of fifth-grade students at SDN Samata, Gowa Regency. The results of the correlation analysis are used to measure the relationship in a research variable. In table 4.7 Analysis Correlations, the correlation value is 0.925 and the sig. value is 0.000 with N = 28. It turns out that the correlation value of 0.925 is greater than the value of the r product moment table, which is 0.374. So r count 0.925> r table 0.374 means that there is a correlation analysis coefficient between Learning motivation and Indonesian language learning achievement of grade V students of SD Negeri Samata, Gowa Regency. The conclusion of the research results is that there is a significant relationship between Learning motivation and Indonesian language learning achievement of grade V students of SD Negeri Samata, Gowa Regency. The greater the value of the correlation coefficient of the variable (X), the greater the value of the correlation coefficient on the variable (Y). This means that the higher the student's Learning Motivation, the higher the Indonesian language learning achievement of grade V students of SD Negeri Samata, Gowa Regency.